Factors influencing home buyers’ purchase decision in Kepala Batas, Pulau Pinang / Syasya Syazana Abdul Halim and Junainah Mohamad - Abdul Halim, Syasya Syazana; Mohamad, Junainah (2023)
Every person should possess a house, house is a decent place to live is seen as a basic human requirement. It offers a physical setting where people and families may take care of their fundamental needs. According to Property Market Report 2020 shows Penang is fourth highest overhang residential property in Malaysia. The study aimed to identify the factors influencing home buyers’ purchase decision in Kepala Batas, Penang and to rank the most influence factor influencing buyer before purchase a house. Before this, Kepala Batas used to be an area of palm oil and rice fields, now it has changed its face into a rapidly developing city, this area keeps develop day by day and lot of residential area was built but there are still many units are unsold. Data collection involved a questionnaire to gather primary data from 199 respondents, while secondary data was obtained from previous studies. Data analysis included descriptive frequencies and ranking to determine the most influential factors. The findings revealed several factors influencing buyers, such as financial considerations, house attributes, location, developer reputation, return on investment, superstitious beliefs, and neighbourhood factors. The study found that the financial factor had the greatest influence, followed by location, neighbourhood, house attributes, developer reputation, return on investment, and superstitious beliefs. Recommendations for future studies include focusing on specific factors, demographic segments, and conducting comparative analysis across different housing markets or regions. In conclusion, the researcher achieved the objectives set forth in the study.